Carbon fibres from renewable resources: the role of the lignin molecular structure in its blendability with biobased poly(ethylene terephthalate). Issue 18 (22nd August 2019) - Beaucamp, Anne; Wang, Yan; Culebras, Mario; Collins, Maurice N.
Abstract : Understanding the blending chemistry at the molecular level to improve lignin valorisation. Abstract : Biobased poly(ethylene terephthalate) has been successfully blended with isopropyl alcohol fractioned hardwood organosolv lignin. The blend compatibility was analysed using Gibbs free energy calculations and confirmed by glass transition temperature measurements as well as morphological studies. The carbon fibres obtained from this blend displayed a turbostratic carbon phase and their morphology exhibited a one phase smooth surface. The carbon yield of the blend was found to be improved by fractionation, reaching values of ∼40%. The chemical structure of lignin, most notably the amount of available aromatic hydroxyl groups, was critical for the success of this work. The high molecular weight fraction is enriched with aromatic hydroxyl groups that can crosslink as ether type bonds such as β-O-4 and β-5 bonds. Upon aliphatic hydroxyl substitution in a modified lignin, the blend with BPET was found to be incompatible and produced a carbon fibre exhibiting two phases, low carbon yield and a low amount of the turbostratic phase.